Mobile Health Application for Patients Undergoing Breast Cancer Surgery: Feasibility Study. Issue 9 (September 2021) - Ponder, Madison; Venkatraman, Vishal; Charalambous, Lefko; Ansah-Yeboah, Abena A.; Adil, Syed M.; Antezana, Luis A.; Dharmapurikar, Rajeev; Gellad, Ziad F.; Lad, Shivanand P.; Hwang, E. Shelley; Plichta, Jennifer K.
Abstract : PURPOSE: Contemporary breast cancer surgery often requires hospital stays of 1 day or less, presenting challenges to delivery of high-quality care. Without sufficient time for proper education and guidance, patients may delay seeking care, experience anxiety, or seek unnecessary care, leading to poorer outcomes and increased costs. To address this, we evaluated the feasibility of a planning-, outcomes-, and analytics-based mobile health application called Manage My Surgery (MMS) for patients undergoing elective breast cancer surgery. METHODS: Patients undergoing breast cancer surgery at an academic health center were invited to use MMS. Those who used the application received pre- and postoperative surveys, which recorded and reported patient satisfaction and outcomes related to the application. RESULTS: Thirty-three female patients undergoing elective breast cancer surgery used MMS. The median age was 58 years. Nineteen patients underwent lumpectomy, and 14 underwent mastectomy. Users logged on to the application an average of 3.5 times. The median number of questions viewed was 12 (range 2-35). Of 17 patients who completed the feedback survey, 100% said that MMS was helpful during preparation for surgery, 82.3% said that MMS was helpful postoperatively, and 94.1% would recommend MMS to others. Preliminary data on patient-reported outcomes collected by MMS suggest improvements in anxiety and depression over time. CONCLUSION: Implementation of a digital care navigation tool in breast cancer surgery patients is feasible. Patients found the tool helpful in both the pre- and postoperative period. Additional ongoing work will focus on patients' self-management skills, long-term outcomes, and health system costs.